Monetary policy wealth effects: Evidence from the 2015 Swiss Franc shock - Martin Brown; Daniel Hoechle; Alejandra Perez; Markus M. Schmid (Swiss National Bank, Study Center Gerzensee, 2025)
This paper studies the transmission of monetary policy to household consumption through wealth effects in a small open economy. As a natural experiment, we exploit the 2015 Swiss franc shock, triggered by the Swiss National Bank's unexpected removal of the euro exchange rate floor. Using granular administrative data from a retail bank, we document substantial consumption responses by households with portfolio exposures to the policy shock. We show that a 1% valuation loss on financial assets is associated with a 0.7% reduction in total spending in the quarter following the shock. This effect is driven by large-ticket spending rather than out-of-pocket spending, attenuates rapidly over time, and depends strongly on the magnitude of the valuation loss. Our results provide direct evidence of a sizeable, immediate, and short-lived wealth channel of monetary policy. They underscore the role of exchange-rate-induced asset revaluations in shaping consumption dynamics in open economies."
Keywords: E52; E58; F31; G51; 330; Household finance; monetary policy; exchange rates; wealth effects; small open economies